Controlled growth of antimony based nanostructured materials by chemical vapor deposition - Chen, Jing (2013)
Sb-based materials have attracted intense attention for a wide range of applications. As demonstrated, Sb-based nanomaterials can achieve enhanced performance, especially in thermoelectric and lithium ion batteries[1-3]. Thus, the controlled growth of Sb based nanomaterials is a major concern in this research field. The attempt of this work was to fabricate Sb-based nanomaterials with tunable sizes by the catalyst-free chemical vapor deposition approach. The study of their growth mechanisms and the effect of growth parameters revealed the effectiveness of this method to prepare nanostructures with controllable sizes. Further measurements on the properties of the as-grown Sb based nanomaterials were conducted to verify the structure-performance relationship. At first, regarding that elements Sb and Te have similar melting points and boiling points, the fabrication of Sb2Te3 nanomaterial through a catalyst-free chemical vapor deposition technique was presented. The obtained Sb2Te3 nanoparticle thin films followed the island growth mechanism. By changing the substrate distance, Sb2Te3 samples varied from micron-sized plates to ~10 nm nanoparticles, which was due to the large difference in substrate temperatures and concentration of precursors. Besides the nanoparticle thin film growth, the catalyst-free chemical vapor deposition could also be applied in the nanowire growth. Based on the consideration that In of low melting point could act as a catalyst during the process to induce one-dimensional growth, the self-catalyzed chemical vapor deposition growth of InSb nanowires was introduced. The vapor-liquid-solid growth process of InSb nanowires was discussed in detail. Due to the difficulty caused by the large condensation temperature gradient between Sb and Cu, it was of special interest to extend the catalyst-free CVD process in growing Cu-Sb alloys. By using copper foils as substrates and the Cu source, Cu-Sb nanostructures were prepared. Simply controlling the substrate distances, Sb-Cu alloy nanostructures, e.g. Cu11Sb3 nanowires, Cu2Sb nanoparticles, or pure Sb nanoplates, were obtained. Such growth strategy could be extended to other Sb alloys, e.g. Co-Sb, Fe-Sb. After fabrication, the property measurement of the as-grown samples was carried out. The as-prepared Sb2Te3 nanoparticle thin film samples showed 100-150% higher Seebeck coefficients and 100-400% lower thermal conductivities as compared with those of bulk Sb2Te3with similar charge carrier concentration. The maximum power factor of above 1.1 10-3 W/mK2 was realized in the annealed 20-nm Sb2Te3 particle film. The InSb nanowires and the Cu2Sb nanoparticle thin film had discharging capacities of ~280 and 278 mAh/g after 50 cycles with 100% and 50% enhancement, as compared with the same materials prepared by other methods. The improved cyclability and reversibility shown in the InSb nanowires and the Cu2Sb nanoparticle thin film was due to the enhanced bonding between active materials and current collectors by the CVD growth. All there results demonstrated that CVD was a promising route to achieve Sb based nanomaterials with enhanced properties.